2016
DOI: 10.18632/oncotarget.13057
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognoses of six patients with multicentric giant cell tumor of the bone

Abstract: Multicentric giant cell tumor of the bone (MGCT) is a rare entity whose radiographic, pathological and biological features remain confusing. We retrospectively reviewed six patients (1 male, 5 female; average age, 22.33 years) treated for confirmed MGCT between 2001 and 2015. The patients' clinical information, images from radiographs (n = 14), CT (n = 13), MRI (n = 8), bone scintigraphy (n = 1) and PET-CT (n = 2), as well as histologic features, treatment and prognosis were analyzed. A total of 17 lesions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…A significant decrease in enhancement in enhanced CT value suggested the decrease of blood supply after denosumab administration [22]. On MRI, marrow replacement by tissue with different signal intensity were reported [18]. For 18F-FDG PET/CT, studies found 94-96% cases underwent denosumab treatment had decreased SUVmax values [10,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant decrease in enhancement in enhanced CT value suggested the decrease of blood supply after denosumab administration [22]. On MRI, marrow replacement by tissue with different signal intensity were reported [18]. For 18F-FDG PET/CT, studies found 94-96% cases underwent denosumab treatment had decreased SUVmax values [10,29].…”
Section: Discussionmentioning
confidence: 99%
“…2). Surgical choice was taken into account by comparing cases underwent curettage with denosumab and curettage alone in 4 studies [9,[16][17][18](OR: 2.13, 95% CI: 0.95 to 4.76, p = 0.07, I 2 = 29%)( Fig. 3), though the result was not statistically significant.…”
Section: Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…1.16 to 4.85, p=0.02, I 2 =57%)(figure2) . Surgical choice was taken into account by comparing cases underwent curettage with denosumab and curettage alone in 4 studies [9,[16][17][18](OR: 2.13, 95% CI: 0.95 to 4.76, p=0.07, I 2 =29%)( Figure 3), though the result was not statistically significant. 7 studies [9,[15][16][17][18][19][20] reported outcome on primary lesions, which also suggest significantly higher risk of local recurrence in the denosumab group(OR: 1.91, 95% CI: 1.17 to 3.09, p=0.009, I 2 =36%)( Figure 4).…”
Section: Recurrencementioning
confidence: 99%
“…On MRI, marrow replacement by tissue with different signal intensity were reported. [18]For 18F-FDG PET/CT, studies found 94%-96% cases 8 underwent denosumab treatment had decreased SUVmax values [10,29]. Ueda et al [11] used CT/MRI and 18FDG-PET/PET-CT to assess objective response of giant cell tumor of bone after denosumab treatment and found a 35%/82%/71% response rate according to RECIST/EORTC/Choi Criteria respectively, suggesting a robust radiographic response after denosumab treatment.…”
Section: Giant Cell Tumor Of Bone Typically Presents As An Eccentric mentioning
confidence: 99%